Prasasti-Prasasti Pendek pada Arca dan Bangunan Keagamaan Masa Bali Kuno - Setiawan, I Ketut (Humanis; Vol 25 No 2 (2021)DO - 10.24843/JH.2021.v25.i02.p11, 2021)
The inscription is one of the very important sources for knowing events in the past. By reading the inscriptions, various aspects of human life can be revealed, such as political, economic, socio-cultural aspects, etc. The research objective was to determine the function and meaning of the inscriptions engraved on sacred statues and buildings. With the strutural functional theory approach and qualitative methods, the results show that language as one aspect of culture provided a lot of information about the dynamics of past societies. The existence of short inscription is very important for the search for the chronology and history of an artifact, in relation to the writing of local history which is still fragmented.